Eigen Value of Fuzzy Matrices - Suroto Suroto; Ari Wardayanti (Journal of Natural Sciences and Mathematics Research, 2016)
In this paper we discuss about eigen value of fuzzy matrices by adopted the substract operation of fuzzy matrices in Sidky and Emam (1992). By applying this substraction, it’s yields that some properties eigen value of fuzzy matrices in Joe Anand and Edal Anand is not satisfied.©2016 JNSMR UIN Walisongo. All rights reserved.